Forest tenure pathways to gender equality: A practitioner’s guide - Jhaveri, Nayna J. (Center for International Forestry Research, 2020)
This practitioner’s guide explains how to promote gender-responsive forest tenure reform in community-based forest regimes. It is aimed at those taking up this challenge in developing countries. There is no one single approach to reforming forest tenure practices for achieving gender equality and women’s empowerment. Rather, it involves taking advantage of opportunities that emerge in various institutional arenas such as policy and law-making and implementation, government administration, customary or community-based tenure governance, or forest restoration at the landscape scale.